2021
DOI: 10.1109/tnsre.2020.3041906
|View full text |Cite
|
Sign up to set email alerts
|

Passive Shoulder Exoskeletons: More Effective in the Lab Than in the Field?

Abstract: Shoulder exoskeletons potentially reduce overuse injuries in industrial settings including overhead work or lifting tasks. Previous studies evaluated these devices primarily in laboratory setting, but evidence of their effectiveness outside the lab is lacking. The present study aimed to evaluate the effectiveness of two passive shoulder exoskeletons and explore the transfer of laboratory-based results to the field. Four industrial workers performed controlled and in-field evaluations without and with two exosk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 41 publications
(57 reference statements)
3
33
1
Order By: Relevance
“…Earlier field studies have indicated that ASEs can reduce physical demands in an actual work environment, as evidenced by reductions in shoulder muscle activity 23,27 and in perceived strain in the neck and shoulders or MSD scores. 21,24 Our results, however, indicate that after accounting for age, body mass, stature, and job demand, using an ASE had little impact on perceived work intensity or MSD scores (Figure 3).…”
Section: Ase As a Moderator To Reduce Physical Demandsmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier field studies have indicated that ASEs can reduce physical demands in an actual work environment, as evidenced by reductions in shoulder muscle activity 23,27 and in perceived strain in the neck and shoulders or MSD scores. 21,24 Our results, however, indicate that after accounting for age, body mass, stature, and job demand, using an ASE had little impact on perceived work intensity or MSD scores (Figure 3).…”
Section: Ase As a Moderator To Reduce Physical Demandsmentioning
confidence: 99%
“…To support the safe adoption and use of EXOs in practice, however, field-based evidence is critical to an understanding of actual effectiveness, practicality, safety, and user acceptance. 19,20 Some work has been reported from field testing of EXOs, ranging from less than an hour to up to a 3-month period, in automotive assembly, 9,[21][22][23][24] manufacturing, 25 warehousing, 26,27 and agriculture settings. 28,29 Arm-support exoskeletons (ASEs) were typically fieldtested for jobs that involve overhead assembly and overhead lifting, while back-support exoskeletons (BSEs) were tested for jobs that involve manual material lifting, shoveling, or require prolonged trunk bending.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These exoskeletons assist individuals working in jobs that require arm elevation, such as supporting the weight of the arms or a tool during overhead work. Yin et al, 2020;Bock et al 2021). However, there are some limitations of this type of approach that are worth noting.…”
Section: Introductionmentioning
confidence: 99%